Utilizing Songs and Stories on Second Language Vocabulary Acquisition - Fayad, By: Al-Mahdi Juma; Mohammed, Hajer Said (مجلة كلية الاداب, 2022)
This study was conducted to investigate the effectiveness of using songs and stories on second language vocabulary acquisition for the first semester English Department students during the academic year 2012-2013. The study was an attempt to answer the following research questions: (i) Can songs and stories be an effective activity for teaching vocabulary? (ii) Will songs and stories enhance students' acquisition of vocabulary more effectively? The results of this study showed that songs and stories positively improved the level of the students.